Role of Nursing Competencies for Accelerating Clinical Trials in Stem Cell Clinics. (3rd November 2017) - Perrin, Mary; Kim, Teresa; Stan, Rodica; Giesie, Pamela; Tabor, Jason; Le Verche, Virginia; Johnson, Shirley; Lomax, Geoffrey P.; Zaia, John A.
Summary : The California Institute for Regenerative Medicine has formed a group of clinics called the Alpha Stem Cell Clinics Network. Its goal is to accelerate clinical trials of stem cell-based therapies for diseases with unmet medical needs. In this report, we describe our experience in establishing an Alpha Stem Cell Clinic at City of Hope. Implementation and integration of the clinic into the existing institutional structures required collaboration and cooperation with clinical trial units, nursing administration, and creation of new positions. The highlight of this process and the centerpiece to our success has been the definition of the role of the "hybrid nurse, " a person with nursing competencies in both clinical care and research. Abstract Video Link: https://youtu.be/WOeZrNyXkGU